Development of PVTX-405 as a potent and highly selective molecular glue degrader of IKZF2 for cancer immunotherapy - Zhixiang Chen; Harshil Dhruv; Xuqing Zhang; Rohan Kalyan Rej; Longchuan Bai; Donna McEachern; Paul Kirchhoff; Rakesh Nagilla; Larry J. Jolivette; Cory T. Rice; Peter Orth; Corey O. Strickland; et al. (Nature Communications)
Abstract IKZF2 (Helios) is a transcription factor that is selectively expressed by Tregs and is essential for preserving the function and stability of Tregs in the tumor microenvironment (TME), where it suppresses the anti-tumor immune response. Targeted IKZF2 degradation by small molecules represents a promising strategy for the development of a new class of cancer immunotherapy. Herein, we describe the discovery of PVTX-405, a potent, effective, highly selective, and orally efficacious IKZF2 molecular glue degrader. PVTX-405 degrades IKZF2 (DC50 = 0.7 nM and Dmax = 91%) while sparing other CRBN neo-substrates. Degradation of IKZF2 by PVTX-405 increases production of inflammatory cytokine IL-2 and reduces the suppressive activity of Tregs, leading to an increase in Teff cell proliferation. Once-daily oral administration of PVTX-405 as single agent significantly delays the growth of MC38 tumors in a syngeneic tumor model using humanized CRBN mice. PVTX-405 in combination with anti-PD1 or anti-LAG3 significantly increases animal survival compared to anti-PD1 or anti-LAG3 alone. Together, these results demonstrate that PVTX-405 is a promising IKZF2 degrader for clinical development for the treatment of human cancers.